An Overview of Clinically Imperative and Pharmacodynamically Significant Drug Interactions of Renin-Angiotensin-Aldosterone System (RAAS) Blockers - Mohamed Pakkir Maideen, Naina; Balasubramanian, Rajkapoor; Muthusamy, Sudha; Nallasamy, Venkateswaramurthy (Current Cardiology Reviews, 2022)
Introduction: Hypertension is a leading cause of cardiovascular disease and chronic kidney disease, resulting in premature death and disability. The Renin-Angiotensin-Aldosterone System (RAAS) blockers, including Angiotensin-Converting Enzyme (ACE) inhibitors or Angiotensin Receptor Blockers (ARBs), are used as first-line antihypertensive therapy to treat hypertensive patients with comorbidities, including diabetes, ischemic heart disease, heart failure, and chronic kidney disease. The use of RAS blockers is associated with the risks, such as hyperkalemia, angioedema, etc. The drugs potentiating them interact pharmacodynamically, resulting in adverse consequences. This review article focuses on the clinically important drug interactions of RAAS blockers. Materials and Methods: The electronic databases, such as Medline/PubMed Central/PubMed, Google Scholar, ScienceDirect, Cochrane Library, Directory of Open Access Journals (DOAJ), Embase, and reference lists were searched to identify relevant articles. Results: The risk of hyperkalemia may be enhanced potentially in patients receiving a RAS blocker and potassium-sparing diuretics, potassium supplements, trimethoprim, adrenergic betablockers, antifungal agents, calcineurin inhibitors, pentamidine, heparins or an NSAID, concomitantly. The patients taking ACE inhibitors and mTOR inhibitors, DPP4 inhibitors, alteplase, or sacubitril/valsartan concurrently may be at increased risk of developing angioedema. Conclusion: Clinicians, pharmacists, and other healthcare practitioners should be accountable for medication safety. To avoid adverse implications, prescribers and pharmacists must be aware of the drugs that interact with RAAS blockers.
Keywords: angiotensin receptor blockers